2017
DOI: 10.1001/jama.2017.8372
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and Management of Asthma in Adults

Abstract: Asthma is characterized by variable airway obstruction, airway hyperresponsiveness, and airway inflammation. Management of persistent asthma requires avoidance of aggravating environmental factors, use of short-acting β2-agonists for rapid relief of symptoms, and daily use of inhaled corticosteroids. Other controller medications, such as long-acting bronchodilators and biologics, may be required in moderate and severe asthma. Patients with severe asthma generally benefit from consultation with an asthma specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 74 publications
1
154
0
4
Order By: Relevance
“…Only a few (1%) used biological treatments but at the time of the study only one biological treatment was available for asthma. Recent recommendations favor biological treatments instead of regular oral corticosteroids in severe asthma [25, 26]. In Finland, results of the public health programs for asthma (1994–2014) and for all allergic conditions (2008–2018) have shown that early treatment with conventional drugs is effective [27].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few (1%) used biological treatments but at the time of the study only one biological treatment was available for asthma. Recent recommendations favor biological treatments instead of regular oral corticosteroids in severe asthma [25, 26]. In Finland, results of the public health programs for asthma (1994–2014) and for all allergic conditions (2008–2018) have shown that early treatment with conventional drugs is effective [27].…”
Section: Discussionmentioning
confidence: 99%
“…There are several asthma phenotypes, among which allergic asthma can be highlighted as the most frequent . The variable degrees of bronchoconstriction, mucus hypersecretion and inflammatory process, triggered by exposure to the allergen, results in the most common symptoms – coughing, wheezing and shortness of breath …”
Section: Introductionmentioning
confidence: 99%
“…1 The variable degrees of bronchoconstriction, mucus hypersecretion and inflammatory process, triggered by exposure to the allergen, results in the most common symptomscoughing, wheezing and shortness of breath. 2 The allergic immune response begins with allergen contact with the epithelium in the lungs, promoting its activation and the release of thymic stromal lymphopoietin (TSLP), interleukin-25 (IL-25) and IL-33. 3 These cytokines trigger activation and migration to the peripheral lymphoid organs of dendritic cells (DCs), where they prime T cells to polarize to T helper type 2 (Th2) [4][5][6] and follicular helper T (Tfh) profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The increased exposures that racial minorities experience in substandard housing likely contributes to disparities in sensitization [12]. This has been demonstrated in multiple studies including: (1) The National Health and Nutrition Examination Surveys (NHANES) III study of 10,508 individuals, in which non-Hispanic black individuals were more likely than non-Hispanic white individuals to be atopic (62% versus 51.3%, OR = 1.6 95% confidence interval 1.2-1.8) [13]; (2) The Boston Epidemiology of Home Allergens and Asthma study, in which black women were 2.5 times more likely than white women to be sensitized to more than 3 allergens, including dust mite, dog, cat, cockroach, alternaria and aspergillus species [14]; and (3) A study in Hartford Connecticut in which Puerto Rican children with asthma were more likely than white children to be sensitized to indoor allergens such as cockroaches (OR 3.3 95%CI (1.7-6.4) and dust mites (OR 1.7 CI 1.2-2.4) [15].…”
Section: Health Disparities In Asthmamentioning
confidence: 97%